Risk Factors of Prenatal and Postnatal Depression - Kartini, Monica; Kusumadewi, Berlian Nurtyashesti (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: The postpartum period is the time when many women or mothers ex